The thermospheric auroral red line Angle of Linear Polarization. Issue 7 (23rd July 2016) - Lilensten, Jean; Barthélemy, Mathieu; Besson, Gérard; Lamy, Hervé; Johnsen, Magnar G.; Moen, Jøran
Abstract: The auroral red line at 630 nm is linearly polarized. Up to now, only its Degree of Linear Polarization had been studied. In this article, we examine for the first time the Angle of Linear Polarization (AoLP) and we compare the measurements to the apparent angle of the magnetic field at the location of the red line emission. We show that the AoLP is a tracer of the magnetic field configuration. This opens new perspectives, both in the frame of space weather and in the field of planetology. Key Points: First calibrated measurement of the auroral red line Angle of Linear Polarization (AoLP) The AoLP is a tracer of the magnetic field configuration It has impacts in space weather and planetary researches